Stereotip Perempuan dalam Cerita Pendek “a Story for Children” Karya Svava Jakobsdottir - Nirmala Khairunnisa Budi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to describe the relationship between men and women who have been socially constructed in the short story A Story for Children by Svava Jakobsdottir. The method used is descriptive analysis combined with structure of the story and gender studies. Data collection uses documentation techniques with steps, such as reading, marking, and classifying. The structure of the story is used to find out the elements depicted in the story. Gender studies are used to determine the position of women who have been socially constructed in the story. The analysis technique used is to observe conditions that occur to women who act as mother and wive. The analysis shows that there are stories about women who are considered able to take care of homework and do not have power in their own home. Conclusion is women who are socially constructed to be able to do homework, follow the husband’s decision, and patience in caring for children. Keywords: Woman, Mother, Wife, Household, Socially Constructed